Employees at Sunset Lumber Company - Giroux, Eugene G. (photographer):::Creator::::::::::::; Tucker, John O., d. 1928 (studio):::Contributor::::::::::::
Group portrait of employees of the Sunset Lumber Company posing on and in front of trucks full of lumber, a few men are posing on bicycles. The company names and products are painted in white on the front of the building. Sunset Lumber specialized in mill work and sash doors.